Immigrants, their children, and theories of assimilation: family structure in the United States, 1880–1970 - Gratton, Brian (2007)
This research employs United States census data from 1880 to 1970 to assess the influence of ethnicity and generation on the family structure of Mexican, Irish, Swedish, Italian, Polish, and native white children. Using evidence for three generations, it tests two theories, linear assimilation and segmented assimilation. Assimilation theory makes no special claims for ethnic effects, but segmented assimilation proposes that ethnicity influences the incorporation of immigrant-origin children into American society. We find few consistent ethnic effects on the probability of family type. Our principal finding is that migration itself, common to all groups, has similar consequences for all; these are revealed in generational changes in family structure. The historical periods of open immigration do differ from the contemporary period, which implies that immigration policy affects family structure. The results disconfirm segmented assimilation theory’s emphasis on ethnicity in family structure, and confirm aspects of linear assimilation theory. They point to the salience of structural factors resulting from migration experience and policy, rather than ethnicity, in the evolution of family form among immigrant-origin persons.